Research on the Ground Subsidence Mechanism of Cross Passage Caused by Freezing Method Construction - Ruimin Zhang; Xuelei Cheng; Yan Li; Lin Pan; Jinhong Xia (Advances in Civil Engineering)
At present, the built or newly built underground structures are mostly concentrated in developed areas along the coast, lakes, and rivers, while deep soft soil is widely distributed in these areas. The cold heat treatment method is one of the advanced foundation treatments and has broad application prospect. However, geothermal exchange and temperature field change are complex Stefan problems with mobile boundaries, internal heat sources, and phase changes. It is important to determine the freezing area and freezing temperature reasonably under the premise of ensuring the safety of the frozen construction. Therefore, this paper summarizes the research methods of freezing method construction of cross passage and introduces the research on the constitutive model of freezing undisturbed soil, the theory of freezing wall calculation, and the evolution mechanism of the temperature field. Then, a brief evaluation is made in view of the lack of research, and the development direction of this field is put forward with the research characteristics. It is to deepen the understanding of the deformation mechanism of cross passage embedded in soft soil caused by the freezing and melting.